Investigating the effect of autograft diameter for quadriceps and patellar tendons use in anterior cruciate ligament reconstruction: a biomechanical analysis using a simulated Lachman test - Amirouche, Farid; Solitro, Giovanni Francesco; Gligor, Brandon Zachary; Hutchinson, Mark; Koh, Jason (Frontiers in Surgery, 2023)
Introduction: Current clinical practice suggests using patellar and quadriceps tendon autografts with a 10 mm diameter for ACL reconstruction. This can be problematic for patients with smaller body frames. Our study objective was to determine the minimum diameter required for these grafts. We hypothesize that given the strength and stiffness of these respective tissues, they can withstand a significant decrease in diameter before demonstrating mechanical strength unviable for recreating the knee's stability.We created a finite element model of the human knee with boundary conditions characteristic of the Lachman test, a passive accessory movement test of the knee performed to identify the integrity of the anterior cruciate ligament (ACL). The Mechanical properties of the model's grafts were directly obtained from cadaveric testing and the literature. Our model estimated the forces required to displace the tibia from the femur with varying graft diameters.The 7 mm diameter patellar and quadriceps tendon grafts could withstand 55-60 N of force before induced tibial displacement. However, grafts of 5.34-and 3.76-mm diameters could only withstand upwards of 47 N and 40 N, respectively. Additionally, at a graft diameter of 3.76 mm, the patellar tendon experienced 234% greater stiffness than the quadriceps tendon, with similar excesses of stiffness demonstrated for the 5.34-and 7-mm diameter grafts.The patellar tendon provided a stronger graft for knee reconstruction at all diameter sizes. Additionally, it experienced higher maximum stress, meaning it dissociates force better across the graft than the quadriceps tendon. Significantly lower amounts of force were required to displace the tibia for the patellar and quadriceps tendon grafts at 3.76-and 5.34-mm graft diameters. Based on this point, we conclude that grafts below the 7 mm diameter have a higher chance of failure regardless of graft selection.